Relation between Parkinson's Disease Severity and Cognitive Function with Monstreal Cognitive Assessment Indonesia - Nasution, Amalia Noor Zafira; Rambe , Aldy S; Hutagalung , Haflin Soraya (CoinReads Media Prima, 2023)
Introduction: Parkinson disease is a wide-spectrum disease that can be accompanied by motor and non-motor symptoms. Non-motor symtoms can occurred before the existance of motoric symptoms until the terimal stage of the disease, where cognitive disturbance is one of the non-motor symptoms that can decrease patient’s quality of life and increase patient’s disability. Therefore, early detection of the cognitive function is important for patients with parkinson disease. The aim of this study was to find the association between the severity of Parkinson’s disease and cognitive disturbance using the Montreal Cognitive Assesment Indonesian version (MoCA-Ina) Method: This study used cross-sectional design. The research subject was a parkinson disease patients’ who went to Neurology Clinic at Haji Adam Malik General Hospital Medan and network hospital who met the inclusion and exclusion criteria of the study. The number of sample was 39 subjects. To determine the relationship between the severity of parkinson disease and cognitive function, the Gamma test was used. Results: There was a significant correlation between the severity of Parkinson's disease and cognitive function (p = 0.001, r = -0.858). There was a very strong correlation between the severity of Parkinson's disease and cognitive function, and the negative correlation means the higher the severity of disease, the lower the cognitive function. From this study, the most correlated domains were delayed memory, naming (r = 0.962), orientation (r = -0.944), visuospatial (r = -0.929), abstraction (r = -0.874), language (r = -0.674), attention (r = -0.592). Delayed memory could not be statistically analyzed because delayed memory were all impaired in all subjects. Conclusion: There was a correlation between the severity of Parkinson's disease and cognitive function with a very strong correlation strength. The cognitive function domains that correlate strongly with Parkinson's severity were delayed memory, naming, orientation, visuospatial and abstraction.